Invert syrup from soft candy scrap by physical and chemical methods - Beza, Carina G.; Gatchalian, Miflora M. (1975.)
Invert syrup was produced from soft candy scrap by physical and chemical methods employing suction filtration, acid treatment, depuration and vacuum concentration. The variables studied were the pH of inversion, kind and amount of decolorizer, and method of concentration. Objective tests show that the best invert syrup was that made from a 55°Brix scrap solution, acid treated at pH 3.3, decolorized with 1% bone char, and concentrated by vacuum heating. The final product had physical and chemical properties similar to those of commercial glucose.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Syrups; Candy